A High Power Density Low Voltage Static Var Generator Based on Wide Band Gap Semiconductor Devices - Dongdong Chen; Weidong Hong; Shengqi Zhang; Xielin Shen; Yanqiang Lin; Hongyi Lin (IEEE Access)
The conventional Static Var Generator (SVG) usually uses IGBT as the power device whose switching loss is high, and switching frequency is low, so the size of output filter and heat sink are large, which limits the improvement of its power density and efficiency. The switching frequency of SiC-MOSFET can be more than twice that of IGBT, and it can withstand higher junction temperature, so that the efficiency and power density of SVG devices can be further improved. This paper optimized the design of SVG from the perspectives of inverter topology, switching frequency, power device loss, device cost, filter, heat sink, etc., and proposed a 220V/50kVar SVG based on SiC-MOSFET discrete devices. It is two-level interleaved as the power topology, a single inductance filter as the filter, and its equivalent switching frequency could reach 100 kHz. The volume of the prototype built is 37L, 66% of the conventional IGBT-SVG product, and the power density is 1.35kVar/L, which is 1.62 times that of the conventional IGBT-SVG product. The peak efficiency of the prototype is as high as 99.03%, and the efficiency is up to 98.75% at full load.